English Teacher’s Competence in Digital Era: A Study on the Development of Teacher’s Ability to Assess Learning Achievement in Pendidikan Profesi Guru - Sibarani, Berlin; Pandia, Betharia Sembiring (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
In digital era, internet, computer, mobile phone, application, ChatGPT, googling, etc. affect education. Googling can translate texts from Indonesian into English and vice versa. It can be used to seek information about linguistics. ChatGPT is able to generate ideas, edit, find main idea, write a summary of English text and do many others. Assessment is useful in providing feedback, developing instructional materials and selecting suitable teaching technique. This paper is intended to describe how Pendidikan Profesi Guru (PPG), as in-service training program, develop English teachers’ assessment competence and to what extent the program accommodate current digital technology. Fifteen English teachers attending the PPG were taken as participants. Data were taken from the observation transcripts, lesson plans and teaching materials. Assessment theory and digital technology information were used as the data analysis perspective. The study shows that (1) the English teacher’s assessment competence is deviated from linguistic, language learning, and language teaching methods theories, (2) technology product effect on test taker has not yet been considered in the language learning, (3) the teachers’ assessment competence is affected by the PPG’s programs which does not provide them with the knowledge of the interrelationship among linguistic, language learning and language teaching method theories, and which has not yet taken the technology effect on test taker into their training program. In order to increase the teacher’s assessment competence, it is suggested that the PPG should be reorganized by accommodating linguistic, language learning, language teaching methods, and technology effect on assessment. Key Words: Assessment, Digital, Language, English, Competence, In-Service Training